Descentralização e provisão de serviços públicos: evidências a partir da criação de municípios brasileiros no setor de saneamento básico - Rocha, Maúna Soares de Baldini (2009)
This paper investigates one of the benefits of fiscal decentralization: better alignment of the basket of public goods with the preferences of the citizens concerned (Tiebout, 1956, Oates, 1972). Based on the method proposed by Ravalion (1999), we use the successive secession of Brazilian municipalities over the past decade (1016 municipalities created) to determine whether the breakup into smaller municipalities reads to better performance in terms of public spending on water and sewerage services. Our results suggest that seceded municipalities invest more on those publicly provided goods and have a better response, in terms of investment on water services, to low water supply indicators compared to the ones that never seceded. Last, we find no evidence that new municipalities invest differently from their originating counterparts.